2023
DOI: 10.1002/ijc.34676
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world treatment patterns and outcomes of pyrotinib‐based therapy in patients with HER2‐positive advanced breast cancer (PRETTY): A nationwide, prospective, observational study

Abstract: Pyrotinib, an irreversible pan‐ErbB inhibitor, has been approved for treating HER2‐positive advanced breast cancer in China. We conducted a nationwide, prospective observational study to examine the real‐world data of pyrotinib‐based therapy in this population. Patients from 61 sites across China were included. Pyrotinib‐based regimens were prescribed at local physician's discretion. Demographics, treatment patterns, prognosis and safety were evaluated. The primary outcome was real‐world progression‐free survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…This result was consistent with the real‐world data of PRETTY trial, which indicated pyrotinib‐based regimens could result in similar PFS in different hormone receptor status. 30 Considering the interaction between estrogen receptor and the human epidermal growth factor receptor family, 31 dual hormone receptor and HER2 pathway targeted therapies could be a rational regimen of maintenance therapy for hormone receptor‐positive/HER2‐positive MBC.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with the real‐world data of PRETTY trial, which indicated pyrotinib‐based regimens could result in similar PFS in different hormone receptor status. 30 Considering the interaction between estrogen receptor and the human epidermal growth factor receptor family, 31 dual hormone receptor and HER2 pathway targeted therapies could be a rational regimen of maintenance therapy for hormone receptor‐positive/HER2‐positive MBC.…”
Section: Discussionmentioning
confidence: 99%